Cerebrospinal fluid penetration of very high-dose meropenem: a case report - Thomas Kerz; Friederike D. von Loewenich; Jason Roberts; Axel Neulen; Florian Ringel (BMC, 2018)
Abstract Background Standard dosing of meropenem (2 g t.i.d.) produces CSF concentrations of only 1-2 mg/L which is inferior to the clinical breakpoint for most Gram-negative bacteria. There is therefore concern that dosing must be increased in order to achieve therapeutic CSF concentrations for bacteria with susceptibility close to clinical breakpoints. Yet, the effects of high-dose meropenem on CSF concentrations are not well described in literature. We therefore determined meropenem CSF-levels in a patient who was treated with 15 g/day of meropenem. Case presentation Our patient suffered from a brain trauma and an external ventricular drainage was implanted. Later, a carbapenemase-producing Acinetobacter baumannii (OXA-23, NDM-1) was isolated from blood cultures and CSF. The MIC for meropenem was > 32 mg/L (R), and we opted for a combination therapy of meropenem, colistin and fosfomycin. Meropenem was given at an unusual high-dose (15 g/day) with the aim of achieving high CSF concentrations. CSF concentrations peaked at 64 mg/L. Yet, the patient succumbed to an intracranial bleed into a preexisting cerebral contusion. Conclusions High-dose meropenem can achieve CSF levels largely superior to those achieved with commonly recommended dosing regimens. Though our patient succumbed to an intracranial bleed which could be regarded as a severe adverse event, we suggest that meropenem dosing can be increased when pathogens with increased MICs are found in the CSF. More in vivo data are however needed to determine the safety of high-dose meropenem.